Iron Deficiency Anemia in Inflammatory Bowel Disease - Dzikowska , Izabela; Wanat, Joanna; Warunek, Aleksandra; Stefaniak, Daria; Homa, Wojciech; Gronowicz, Gabriela; Siejka, Agata; Zielińska, Weronika; Chról, Michał (Journal of Education, Health and Sport, 2025)
Inflammatory bowel disease (IBD) is a chronic inflammatory disease of the gastrointestinal tract. It includes Crohn's disease (CD) and ulcerative colitis (UC). It occurs with periods of exacerbations and remissions. One of the most common complications of IBD is iron deficiency anemia (IDA). In IBD, iron deficiency anemia (IDA) often occurs concomitantly with anemia of chronic disease, caused by chronic inflammation of the gastrointestinal tract. Disturbance of iron homeostasis in IBD results from inflammation of the intestinal mucosa, which causes increased blood loss from the gastrointestinal tract and poor iron absorption. A key role is played by hepcidin, which, by acting on ferroportin, inhibits iron absorption in the intestines, despite its deficiency. Less common causes of anemia in IBD include vitamin B12 deficiency, folate deficiency, hemolysis, drug-induced aplasia, or liver disease such as primary sclerosing cholangitis. Symptoms of iron deficiency depend on the severity and chronicity of the anemia. Anemia reduces the quality of life of patients, so diagnosis and treatment of iron deficiency anemia in IBD is essential. Regular monitoring of anemia and iron homeostasis is recommended. Tests should be performed at the time of IBD diagnosis, every 3 months in active disease and every 6-12 months in periods of remission. In all patients with IBD, it is necessary to follow an appropriate diet, but also to treat anemia with iron preparations, oral or intravenous. The choice of the method of iron administration, oral or intravenous, depends on the hemoglobin level, IBD activity, and the patient's tolerance to oral preparations. Regular monitoring is essential because anemia in IBD often recurs.